2017
DOI: 10.3310/hta21690
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of methodological search filters to improve the efficiency of evidence information retrieval: five literature reviews and a qualitative study

Abstract: Note to reader: it is acknowledged that there has been a regrettable delay between carrying out the project, including the searches, and the publication of this report, because of serious illness of the principal investigator. The searches were carried out in 2010/11. Published November 2017 DOI: 10.3310/hta21690This report should be referenced as follows:Lefebvre C, Glanville J, Beale S, Boachie C, Duffy S, Fraser C, et al. Assessing the performance of methodological search filters to improve the efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 117 publications
(346 reference statements)
0
40
0
Order By: Relevance
“…While combining these methods is recommended [9], , it may not eliminate bias caused by any one method. Accordingly, ur gold standard sample may not be fully representative of those in the corpus of literature, particularly studies where the inequality is not indexed and reported only in the body of the text.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While combining these methods is recommended [9], , it may not eliminate bias caused by any one method. Accordingly, ur gold standard sample may not be fully representative of those in the corpus of literature, particularly studies where the inequality is not indexed and reported only in the body of the text.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies contained in the reviews we examined may not be representative of the full corpus of literature and important studies may be missed [5]. Further, the reviews we located may not themselves fully represent the sample universe of equity-focused reviews [9]. We hand-searched only a limited number of issues in two journals, and records contained in personal files are unlikely to have broad coverage of the topic area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations